Development of Patisserie Gastronomy Expertise Competency Test Model in Teacher Professional Education of Vocational High School Culinary Program - Ria Rumondang, Juwita; Basyirun, Basyirun; Zahrulianingdyah, Atiek (Journal of Vocational and Career Education, 2019)
The objectives of this study are to (1) produce the development of a competency test model of Patisserie Gastronomy Expertise in the Teacher Professional Education of the Gastronomy Program (Patisserie Gastronomy Expertise Competency Test Model); (2) analyze the instruments (modules and manuals) and (3) evaluate the model so that it meets the criteria for effective, practical, and well implemented. The method used in this research was Research and Development (R&D). The data source came from interviews and questionnaires towards 20 respondents consisting of 5 vocational school teachers of culinary skills competency, patisserie expertise, 5 gastronomy lecturers of UNNES, and 10 executive chef practitioners from Business and Industrial World). The results of the development of the competency test model of Patisserie Gastronomy Expertise Competency in the Teacher Professional Education of vocational culinary program (the Patisserie Gastronomy Expertise Competency Test Model) is a model guide book consisting (a) supporting theory; (b) The purpose of developing the model; (c) Tiered qualifications; (d) The structure and contents of the Patisserie Gastronomy Expertise Competency test model components; (e) Competency Standards and Basic Competencies Â of the Patisserie Gastronomy Expertise Competency Testing Model; (f) The Patisserie Gastronomy Expertise Competency test model approach; (g) Learning/training strategies and methods; (h) Guidelines for valuation; (i) Stages of processing; (j) Time of evaluation; (k) Assessment rubric; (l) Closing. While the competency test sets are: (a) Learning/training modules and tests with good criteria (3.69) and (b) sheets and ability and the rubric of assessment (justification) of training/test with good criteria (3.62).